2013
DOI: 10.1016/j.devcel.2013.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Exo70 Isoform Switching upon Epithelial-Mesenchymal Transition Mediates Cancer Cell Invasion

Abstract: Summary Epithelial-mesenchymal transition (EMT) is an important developmental process hijacked by cancer cells for their dissemination. Here we show that Exo70, a component of the exocyst complex, undergoes isoform switching mediated by ESRP1, a pre-mRNA splicing factor that regulates EMT. Expression of the epithelial isoform of Exo70 affects the levels of key EMT transcriptional regulators such as Snail and ZEB2, and is sufficient to drive the transition to epithelial phenotypes. Differential Exo70 isoforms e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 72 publications
6
77
0
Order By: Relevance
“…This Exo70 isoform cannot interact with the Arp2/3 complex and fails to stimulate cell motility (Warzecha et al, 2010;Lu et al, 2013). Isoform switching of Exo70 takes place during epithelial-to-mesenchymal transition, and is implicated in breast cancer metastasis (Lu et al, 2013). Exo70 was also found to be the most diversified subunit of the exocyst complex in plants -many of them have dozens of Exo70 paralogues per genome.…”
Section: Functional Diversification Of the Exocystmentioning
confidence: 99%
See 1 more Smart Citation
“…This Exo70 isoform cannot interact with the Arp2/3 complex and fails to stimulate cell motility (Warzecha et al, 2010;Lu et al, 2013). Isoform switching of Exo70 takes place during epithelial-to-mesenchymal transition, and is implicated in breast cancer metastasis (Lu et al, 2013). Exo70 was also found to be the most diversified subunit of the exocyst complex in plants -many of them have dozens of Exo70 paralogues per genome.…”
Section: Functional Diversification Of the Exocystmentioning
confidence: 99%
“…During epithelialization, epithelial splicing regulatory proteins 1 and 2 (ESRP1 and ESRP2) mediate the generation of a particular isoform of Exo70 (also known as Exo70-E; Lu et al, 2013) that differs from other Exo70 isoforms by a 23-amino-acid insertion. This Exo70 isoform cannot interact with the Arp2/3 complex and fails to stimulate cell motility (Warzecha et al, 2010;Lu et al, 2013). Isoform switching of Exo70 takes place during epithelial-to-mesenchymal transition, and is implicated in breast cancer metastasis (Lu et al, 2013).…”
Section: Functional Diversification Of the Exocystmentioning
confidence: 99%
“…In humans, EXO70 mediates the trafficking of the glucose transporter Glut4 to the plasma membrane that is stimulated by insulin and involved in the development of diabetes (13). A specific isoform of human EXO70 is also involved in cancer cell invasion (13)(14)(15). Endosidin2 (ES2) was identified from a plantbased chemical screen as an inhibitor of trafficking.…”
mentioning
confidence: 99%
“…Ewald and colleagues found that tumor cells including cytokeratin 14 had greater invasive ability [13]. Guo and colleagues found that Exo70 affected cell structure and movement by bending the cell membrane, which then impacted the cell migration and invasion of a tumor [14]. However, these studies did not incorporate the effects of the surrounding host tissue.…”
Section: Introductionmentioning
confidence: 99%